The Woman's Hour: The Great Fight to Win the Vote - Elaine Weiss (Penguin Books, 2019)
Nashville, August 1920. Thirty-five states have approved the Nineteenth Amendment, granting women the right to vote; one last state--Tennessee--is needed for women's voting rights to be the law of the land. The suffragists face vicious opposition from politicians, clergy, corporations, and racists who don't want black women voting. And then there are the "Antis"--women who oppose their own enfranchisement, fearing suffrage will bring about the nation's moral collapse. And in one hot summer, they all converge for a confrontation, replete with booze and blackmail, betrayal and courage. Following a handful of remarkable women who led their respective forces into battle, The Woman's Hour is the gripping story of how America's women won their own freedom, and the opening campaign in the great twentieth-century battles for civil rights.